Pembangunan Permukiman Prioritas dalam Perspektif Tata Ruang (Studi pada Permukiman Industri Tempe Sanan Kota Malang) - Novinaz Benita (Jurnal Administrasi Publik, 2014)
Abstract: Priority Settlement Development in Spatial Perspective Study at the Tempe Sanan Industrial Settlement Malang City. Priority settlement is the one of Malang City government program and have aims to support the avaibility suitable and arranged settlement and supporting the purpose of Malang development as education, tourism and industrial city or known as Tribina Cita Malang City. There three aims from this research and all analized by spatial perspective, first describes and analyze the criteria of the reason for the stipulation of settlement priority according Settlement Strategy and Urban Infrastructure (SPPIP) Malang, second contribution Settlement Area Development Plan Priority (RPKPP) in the construction industry Tempe Sanan Settlement area as a priority settlements in spatial perspective, third describes and analyze the factors enabling and inhibiting the process of implementing the Settlement Plan Priority Development Zone (RPKPP) in the construction industry Tempe Sanan Settlement area in spatial perspective. The research method used is a qualitative research method with a descriptive approach and uses data analysis Spradley models techniques. The result from this research is determination of priority settlement is based on Strategy Of Settlement Development And Urban Infrastructure (SPPIP) documents and development program for priority settlements refer to Development Plan Of Priority Settlement Regions (RPKPP). As the first priority, Tempe Sanan Industrial Settlement has many problems, especially in spatial structuring and environment condition. Therefore, spatial theory approach is needed to support the successful implementation of development programs in Tempe Sanan Industrial Settlement as the top priority settlement. Â  Keyword: Priority settlement, Tempe Sanan industrial settlement, SPPIP, RPKPP Abstrak: Pembangunan Permukiman Prioritas Dalam Perspektif Tata Ruang(Studi Pada Permukiman Industri Tempe Sanan Kota Malang). Permukiman prioritas merupakan program Pemerintah Kota Malang yang bertujuan untuk mendukung ketersediaan permukiman yang layak dan teratur serta untuk mendukung keberhasilan Tri Bina Cita Kota Malang. Tujuan dari penelitian ini adlalah untuk menganalisis dan mendeskripsikan kriteria penetapan permukiman prioritas berdasarkan dokumen SPPIP, kontribusi program dalam RPKPP untuk Permukiman Industri tempe sanan serta hambatan dan dukungan dalam pembangunan Permukiman Industri Tempe Sanan. Hasil dari penelitian ini adalah Permukiman Industri Tempe Sanan menjadi permukiman prioritas utama karena memiliki karakteristik sesuai dengan kriteria yang telah ditentukan, yakni permukiman yang mampu mendukung keberhasilan Tribina Cita Kota Malang. Dalam proses pembangunan permukiman prioritas, pemerintah Kota Malang mengacu pada dokumen Rencana Pembangunan Permukiman Prioritas (RPKPP) yang didalamnya memuat berbagai program pembangunan yang pada akhirnya akan memberikan kontribusi ekonomi, kontribusi lingkungan dan infrastruktur maupun kontribusi sosial. Namun dalam proses pengimplementasian, terdapat faktor kendala dan dukungan. Oleh sebab itu peneliti menggunakan pendekatan teori tata ruang untuk mendukung kesuksesan dalam proses pembangunan permukiman prioritas. Â  Kata kunci: Permukiman prioritas, permukiman industri Tempe Sanan, SPPIP, RPKPP